Strategies for Promoting Collaboration in Reading Comprehension Lessons among Students with Learning Disabilities - Lazarus, Kelechi Uchemadu (The Center for Disability Studies and Services Brawijaya University, 2021)
Efficient skills in reading comprehension enable secondary school students to make meaningful and remarkable advancements in their studies. However, many students with learning disabilities struggle with reading comprehension and consequently obtain low grades in their academic pursuits. This paper pointed out that improvement in reading comprehension and academic achievement among secondary school students with learning disabilities is possible through engaging the students in collaborative learning activities within reading comprehension context. The paper therefore highlighted the principles that guide collaborative classrooms and the benefits of student collaboration in reading comprehension context. Evidence-based interventions that emphasize collaboration such as cooperative learning, peer tutoring, reciprocal teaching, collaborative strategic reading, and directed reading-thinking activity were discussed. Recommendations were made which include that teachers should ensure that they infuse collaboration into reading comprehension lessons of students with learning disabilities by making use of a variety of teaching strategies that stress collaboration, assigning roles to group members and ensuring that group members adhere to the laid down rules for the groups.